Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus - Xue, Qingquan; Zhang, Yalin (Zootaxa, 2018)
Two new genera of Idiocerini, Lambirocerus gen. nov. with type species Lambirocerus cycloformulus sp. nov. and Undophomorpha gen. nov. with type species Undophomorpha glauctata sp. nov., are described and illustrated from Malaysia. The type species of Paraidioscopus Maldonado-Capriles, P. tagalicus (Baker) is also redescribed and illustrated.